Pengaruh Kepemimpinan Inklusif, Self Efficacy dan Iklim Organisasi Terhadap Perilaku Inovatif Karyawan - Adhelia Putri Salwa; Anak Agung Ketut Diatmika (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Rapid developments in science and technology place organizations in the midst of new challenges and unprecedented opportunities. PT. XYZ, a manufacturing company that specializes in chemical coatings or known as "CAT", emphasizes employees to have innovative behavior. In this company, there is an award program for employees who are able to apply innovative ideas for the company and are willing to convey these ideas to management. This program is the basis for research conducted by researchers at PT. XYZ which operates in Tangerang. This research analyzes the impact of inclusive leadership, self-efficacy, and organizational climate on employee innovative behavior, using survey methods and purposive sampling from 166 PT employees. XYZ Tangerang. This research involved various statistical tests, including validity, reliability, multiple linear regression analysis, as well as coefficient of determination, partial t and simultaneous f tests. The research results show that inclusive leadership, self-efficacy, and organizational climate have a significant influence on employee innovative behavior. These findings provide a better understanding of the relationship between these factors and innovative behavior in the workplace. By ensuring inclusive leadership that creates a supportive environment, increases employee self-confidence, and promotes an innovative organizational climate, an organization can increase the creativity and innovation potential of its teams. These three factors combined can make a significant contribution to increasing employee innovative behavior, which ultimately also strengthens the overall growth and sustainability of the organization.